Improving the Students Ability in Writing Narrative Text through Group Discussion at the Eight Grade of SMP Negeri 2 Sirombu in 2022/2023 - Fondroro Invokafit Daeli; Hidayati Daeli; Riswan Zega; Trisman Harefa (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Writing is one of the ways people convey information and give their opinions on specific topics. As an indispensable part of language communication, writing becomes an essential skill that students must master. However, grade VIII students of SMP Negeri 2 Sirombu have low narrative writing ability. Therefore, the researcher wants to improve students' ability to write narrative texts by conducting group discussions. The researcher used a Classroom Action Research (CAR) method that included two cycles and four meetings to conduct her study. CAR processes include planning, action, observation, and reflection. The survey subject is class VIII-1 of SMP Negeri 2 Sirombu in 2022/2023 with 19 students. The researcher used observation sheets, assessment sheets, and field notes to collect data. From there, the researcher made some suggestions related to the research results, specifically: (1) In teaching writing, teachers first need to motivate students to create great motivation for learning English in general and writing fluently in English in particular; (2) SMP Negeri 2 Sirombu in English teachers should use group discussion method to improve students' ability to write narrative writing, especially fables; (3) Students need to be encouraged to use dictionaries in the process of learning English; (4) SMP Negeri 2 Sirombu English teachers must be able to apply appropriate writing teaching strategies to students. After conducting research by applying the Group Discussion strategy for two cycles and four meetings, this strategy was successfully implemented in class VIII-1 of SMP Negeri 2 Sirombu to obtain good results; there was an increase, as the researchers hoped.